HUBUNGAN ANTARA BEBAN DAN LAMA MESUUNAN DENGAN KELUHAN MUSKULOSKELETAL PADA PEREMPUAN TUKANG SUUN DI PASAR BADUNG DENPASAR - Putu Dwija Arnatha (Coping: Community of Publishing in Nursing, 2014)
Badung Market is one of the largest traditional markets in Bali. In Badung Market tukang suun is lifts groceries items on the head using a basket. Mesuunan leads to injury: damage to the intervertebral discs, causing painful, pain, excessive fatigue, and disorders of the muscles of the head and neck. The recommended maximum lifting load of 30.25 kg or no more than 60% of body weight. The problems caused by mesuunan with excessive load and duration of mesuunan can cause a variety of musculoskeletal complaints. The study aims to determine whether there is a relationship between the load and the duration of mesuunan with musculoskeletal complaints in women of tukang suun in Badung Market Denpasar. The study is a non-experimental survey with cross sectional analytic. The analysis of the data is using Kendal Tau correlation test. The number of samples in the study is 60 women of tukang suun. The result of study shows there is a relationship between the load of mesuunan with significant musculoskeletal complaints (p < 0,05) and there is a relationship between duration of mesuunan with significant musculoskeletal complaints (p < 0,05). Based on the results it is suggested for tukang suun to reduce the burden of mesuunan by modifying the basket of suunan in a smaller form with a normal amount of weight. For subsequent researchers it is expected to examine other factors that affect the musculoskeletal complaints in tukang suun.